Republic of Malawi Diagnostic Trade Integration Study Update : Reducing Trade Costs to Promote Competitiveness and Inclusive Growth - World Bank (Washington, DC, 2014)
The diagnostic trade integration study (DTIS) update identifies the trade related constraints holding back Malawi from diversifying and deepening its production base, and increasing trade. The DTIS update identifies and quantifies specific trade costs that determine the availability and price of inputs and the ability of producers to get their products to regional and international markets. The report focuses on tariff policies, regulatory issues impacting on trade, trade facilitation and logistics, and policies affecting agricultural trade and trade in services. Recognizing that the (enhanced) integrated framework and the DTIS (including the 2003 DTIS for Malawi) have not been effective in addressing many of the broader issues requiring large-scale physical investments in most countries, this DTIS update focuses on specific trade related policy and regulatory issues within the mandate and policy space of the ministry of trade and the national implementation unit or similar implementation mechanisms. In this context, the report is structured as follows: chapter one gives introduction. Chapter two outlines the current macroeconomic position and the level of trade openness, summarizes the status of the business enabling environment. Chapter three describes Malawi's current trade policy with a detailed review of the existing tariff schedules. Chapter four addresses a range of the key regulatory issues that raise costs for all producers in Malawi. Chapter five looks in depth at how the trade and regulatory policies within the agricultural sector impact on competitiveness. Finally, chapter six addresses the important issues of trade in services through focusing on professional services such as engineering, accounting, and law.